From absence to poetics (fragments of amorous discourse in Machado) - Herrera Ávila, Tatiana (2026)
This paper analyzes the poem by AntonioMachado entitled “Other songs to Guiomar” and propo-ses that the text constructs a poetic that is shaped fromthe absence of the beloved, using as points of analysisthe poet’s notion of love and several of the figures propo-sed in Roland Barthes’ A Lover’s Discourse: Fragments.